Fluorite type oxide ion conductors of Bi2O3-M2O5 (M = P, As, V) - Lee, Siew Ling (Penerbit UTM, 2008)
Bi2O3-M2O5, M = P, As, V systems and related materials were prepared by solid state reactions. The phase purity of the materials was determined by X-ray diffraction (XRD). Further characterization using ac impedance spectroscopy and differential thermal analysis (DTA) were carried out on single phase materials. Besides, inductively coupled plasma-atomic emission spectrometry (ICP-AES), density measurement, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), Fourier-transform infrared (FT-IR) spectroscopy and Raman spectroscopy were also performed on selected materials. The crystal system and space group of the single phase materials were determined. Two narrow solid solution series were formed in xBi2O3-P2O5: 5.5 < x < 6 and 7 < x < 7.25. In DTA study, a phase transition was clearly seen in Bi7PO13 and Bi29P4O53.5 at ~860oC. XRD shows that single phase materials were formed in xBi2O3-As2O5 binary system when x = 5, 5.5, 5.667, 5.75, 6 and 7. Among these, materials in the composition range of 5 < x < 6.25 appeared to be solid solutions. Attempts to synthesize materials of composition of xBi2O3-As2O5, 1 < x < 4 were unsuccessful. Single phase materials were formed in xBi2O3-V2O5 binary system, 5 < x < 6 and x = 7. A phase transition was observed in Bi17V3O33 and Bi23V4O44.5 at 180oC. However, its origin is unknown. Materials of composition xBi2O3-M2O5, 5.5 < x < 6 (M = P) and 5 < x < 6 (M = As, V) are refined in triclinic symmetry with space group of P-1. Meanwhile, monoclinic symmetry was found in materials where x = 7, 7.25 (M = P) and x = 7(M = As, V). The XRD and IR patterns of both series of xBi2O3-As2O5, 5 < x < 6.25 and xBi2O3-V2O5, 5.5 < x < 6 solid solutions are very similar since these materials are isostructural. Generally, lattice parameters, volumes and densities of the materials in xBi2O3-M2O5 system, M = P, As, V increased with the increase of Bi content. A complete solid solution series was formed in the Bi22P4O43-Bi22As4O43, Bi22P4O43-Bi22V4O43, Bi22As4O43-Bi22V4O43, Bi23P4O44.5-Bi23As4O44.5, Bi23P4O44.5-Bi23V4O44.5, Bi23As4O44.5-Bi23V4O44.5, Bi12P2O23-Bi12As2O23, Bi12P2O23-Bi12V2O23, Bi12As2O23-Bi12V2O23 and Bi7AsO13-Bi7VO13 systems. In Bi7PO13-Bi7AsO13 and Bi7PO13-Bi7VO13 systems a two-phase region was seen. All the single phase materials studied above appeared to be oxide-ion conductors. Conductivity increased with increasing vanadium content, followed by arsenic and phosphorus. Among the materials prepared, the highest conductivity is obtained in Bi23V4O44.5 with a conductivity value of 1.34 x 10-4 ohm-1 cm-1 at 300oC. In an attempt to optimize oxide ion conductivity, chemical doping using PbO, Sr(NO3)2, Al2O3, Ga2O3, La2O3, Fe2O3 etc. was carried out in selected materials, resulting in the formation of limited solid solutions. These materials, however, exhibit conductivity slightly lower than that of the parent materials. Ball milling process has been carried out in the preparation of Bi23V4O44.5 in addition to manual grinding prior to firing of the samples. In ball milling process, high-density, fine-grained powders with uniform grain-size distribution were obtained, resulting in an increase in conductivity and dielectric constants.